Gas-Phase Carbonylation of Dimethyl Ether on the Stable Seed-Derived Ferrierite - Ham, Hyungwon; Jung, Hyun Seung; Kim, Hyo Seok; Kim, Jihyeon; Cho, Sung June; Lee, Won Bo; Park, Myung June; Bae, Jong Wook (ACS Catalysis, 2020)
The higher catalytic activity and stability for a gas-phase carbonylation of dimethyl ether (DME) to methyl acetate (MA) on the seed-derived ferrierite (FER) were attributed to its higher crystallinity with small amounts of defect sites by recrystallization methods without using any organic structure directing agent. The recrystallized FER (FER-S1) with its smaller amount of Lewis acidic extraframework Al sites (EFAl) possessed proper number of Brønsted acidic sites in the eight-membered-ring (8-MR) channels in comparison to the pristine FER, which was responsible for an enhanced CO insertion rate to methoxy intermediates formed by dissociated DME molecules by referentially forming acetyl intermediates or to the highly active Brønsted acidic sites. The most active tetrahedral T2 sites with two adjacent Al atoms in the 8-MR channels having next-nearest Al-O-Si-O-Al configurations on the FER-S1 revealed the stronger adsorption of the stably adsorbed DME molecules as confirmed by DFT calculations. FER-S1 containing the proper amounts of Al atoms in the 8-MR with appropriate locations with optimal acidic properties was responsible for its higher activity and stability for the gas-phase carbonylation of DME, where the Al distributions were confirmed by Rietveld refinement XRD analysis, FT-IR, and DFT calculations. In addition, the acidic sites on the outer surfaces and larger cavity including 10-MR channels were responsible for an accelerated formation of aromatic coke precursors.
Keywords: Acidic properties; Coke precursors; DFT calculation; Dimethyl ethers; Extra-framework Al; Insertion rates; Methyl acetates; Organic structures; Al distributions in FER channels; dimethyl ether (DME); gas-phase carbonylation; methyl acetate (MA); seed-derived ferrierite (FER); stability and deactivation